Jahresbericht 1983 - Kunstgesellschaft Luzern : Bernhard Eglin-Stiftung 50 Jahre - Kunstmuseum im Kunsthaus. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1984)
Longobardi, Nino ; Salvo ; Meyer, Rolf ; Wiget, Maria-Louisa ; Bucher, François ; Roth, Dieter ; Acconci, Vito ; Bauermeister, René ; Egloff, Anton ; Gerz, Jochen ; Kielholz, Heiner ; Luethi, Urs ; etc.
Duits
boek